India's tryst with destiny - Bhagwati, Jagdish N. (HarperCollins Publishers, 2012)
Policy discourse in India tends to be dominated by assertions unsupported by facts, with the media indulging one and all without proper scrutiny. Often, the result is the creation and perpetuation of myths of all kinds. Thus, many believe today that poverty, illiteracy and ill-health afflict India because its leadership ignored them in favour of growth for its own sake; that the economic reforms that focused on growth have failed to help the poor, especially the socially disadvantaged; that any gains claimed in poverty alleviation derive from the use of progressively lower poverty lines; and that even if gains have been made, with one in two children suffering from malnutrition, reforms have done precious little to improve health outcomes